PARENTING STYLES AND ADOLESCENTS’ BEHAVIOUR IN CENTRAL EDUCATIONAL ZONE OF CROSS RIVER STATE - Mbua, Anake, P.; Adigeb, Ada P. (European Scientific Journal, ESJ, 2015)
Transitional period or stage of physical and psychological human development creates in the adolescents a feeling of tension between dependency on their parents and the need to break away. Tension and behaviour disorder, disagreement increases as friends demonstrate a greater impact on one another, new influences on the adolescents that may be in opposition to parents’ values. All these conflicts create in parents mixed feelings and makes parenting a complex task, with specific parenting practices which are less important in predicting child well-being. Base on this the researcher was interested in investigating parenting styles and its influences on adolescents’ behaviour. Null hypothesis was formulated to guide the study. Review of literature was carried on accordingly. A sample of 627 respondents was selected for the study. The selection was done through the stratified and simple random sampling techniques. Questionnaire was the main instrument for data collection. A one-way analysis of variance (ANOVA) was adopted. The hypothesis was tested under a 0.05 level of significance. The result of the analysis revealed that parenting styles significantly influence adolescents’ behaviour. Recommendations were made based on the result; that parents and adolescents should maintain cordial relationship and interaction to guide against behaviour misconduct and family conflict, leading to depression, anxiety, aggression and worries on the growing person.